Statistical Optimization Of Cultural Conditions For Manganese Peroxidase Production By Coriolus Versicolor Mtcc 138 From Digested Cattle Dung Slurry (Applied Biological Research, 2017)
The present study reports the production of manganese peroxidase enzyme  using digested cattle dung slurry as a substrate by Coriolus versicolor MTCC  Digested cattle dung slurry was analyzed for proximate (total solids,  volatile solids and pH), chemical (cellulose, hemicellulose, lignin and silica) and biochemical (total proteins and manganese peroxidase) composition. Manganese peroxidase production by C. versicolor MTCC 138, was optimized by a conventional ‘one variable at a time approach’ and then by Placket Burman design. Optimized fermentation conditions for the maximum  manganese peroxidase (78.0 U mL-1) enzyme production were 25% slurry concentration, 5 days of incubation, temperature 25°C and inoculum size of 106  spores mL-1. This enzyme titre obtained by statistical optimization was 1.86- fold than that achieved by ‘one variable at a time approach’. It revealed that the effect of different cultural conditions (slurry concentration, spore concentration and incubation period) have statistically significant effect on enzyme production.
Keywords: Coriolus versicolor MTCC 138; digested cattle dung slurry; manganese peroxidase; Placket-Burman model